Alcohol Use, Risk Taking, Leisure Activities and Health Care Use Among Young People in Northern Vietnam - Le Thi Kim Thoa; Dang H. Hoang; Nguyen Dang Vung; Pham H. Tien; M. A. Plant (University Library System, University of Pittsburgh, 2013)
Alcohol consumption is associated with a wide range of health and social consequences. It is also associated with a number of risk taking behaviours. These include illicit drug use and unsafe sex.  Alcohol consumption appears to be increasing in Vietnam. The purpose of this paper is to examine the patterns of alcohol consumption and its relationship with a number of other risk taking behaviours amongst young people.  Information was also obtained concerning leisure activities and use of health care. The paper also sets out to examine possible gender differences in relation to alcohol consumption and risk behaviour and to propose the development and implementation of alcohol monitoring and prevention programs in Vietnam.  The study involved a cross-sectional, community survey using a standardised interview.  This was conducted during face-to-face interviews with 1,408 young people aged 10-19 years.  Respondents were recruited randomly through the lists of the households from 12 selected communes in three areas in Northern Vietnam. The findings presented here were part of a larger health risk behaviour survey.  Levels of alcohol use were low. Overall, 16.5% of participants were experienced drinkers, and only 4% of them were current drinkers. Males were significantly more likely than females to report drinking. This study also showed that rates of alcohol consumption were associated with age, education, geographical area, gender, tobacco smoking, involvement in violence, watching television, computer use and playing computer games, wearing safety helmets and use of health services. Alcohol consumption tended to increase with age for both males and females.  Alcohol and its effects on young people are clearly a growing public health issue in Vietnam.  Because of this, more detailed behavioral research should be conducted into the relationship between alcohol consumption and other risky behaviours amongst young people.  It is also recommended that alcohol harm reduction policies should be implemented and integrated into measures to reduce levels of other health problems such as HIV/AIDS and non communicable diseases. Such policies should ideally be evidence-based and evaluated.